Neural Response Telemetry Thresholds in Patients with Cochlear Nerve Canal Stenosis. (2nd July 2015) - Han, Shuguang; Wang, Line; Zhang, Daoxing; Peng, Kevin
Abstract : Objective: To explore neural response telemetry (NRT) thresholds in patients with stenotic versus normal cochlear nerve canals. Study Design: Case series with chart review. Setting: Tertiary referral center. Subjects and Methods: Thirty pediatric patients with profound sensorineural hearing loss in at least 1 ear and no benefit from amplification underwent computed tomography imaging of the temporal bones. They were divided into 3 groups according to the diameter of the cochlear nerve canal: group A, <1.5 mm; group B, 1.5 to 1.7 mm; group C, 1.8 to 2.1 mm. All patients underwent cochlear implantation with full insertion of all electrodes. NRT was performed both intraoperatively and 6 months postoperatively in all patients; thresholds of electrodes 1, 11, and 22 were compared. Results: Per analysis of variance, intraoperative and 6‐month postoperative NRT thresholds were both significantly different among groups A, B, and C at electrodes 1 and 22 but not at electrode 11. On intergroup analysis, group A showed statistically higher thresholds than those of groups B and C; however, no difference was found between groups B and C. Conclusion: Cochlear nerve canal stenosis, defined as a canal diameter <1.5 mm, is associated with significantly increased NRT thresholds, which may play a role in postimplant performance.